2018
DOI: 10.1111/tri.13352
|View full text |Cite
|
Sign up to set email alerts
|

Obesity does not significantly impact outcomes following simultaneous liver kidney transplantation: review of the UNOS database - a retrospective study

Abstract: Summary Simultaneous liver kidney transplantation (SLK) is the only curative option for patients with combined end stage liver and kidney disease. With the global obesity epidemic, an increasing number of obese patients are in need of SLK. However, the impact of pre‐transplant obesity on outcomes after SLK is unknown. An analysis of the United States OPTN registry (Oct 1987 – June 2016) identified 7205 SLK transplants. Of these, 1677 patients were overweight/obese (OW, BMI 30–39) and 183 were morbidly obese (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Obesity is also associated with increased incidence of recurrence of HCC for patients with HCC undergoing LT (19). Contrary to most data identifying obesity as a risk factor for graft survival, a retrospective study of UNOS database showed that BMI is not a risk factors for poor patient and both liver and kidney graft survival (20). This study analyzed 7,205 SLK transplants.…”
Section: Pre-lt Obesitymentioning
confidence: 82%
See 1 more Smart Citation
“…Obesity is also associated with increased incidence of recurrence of HCC for patients with HCC undergoing LT (19). Contrary to most data identifying obesity as a risk factor for graft survival, a retrospective study of UNOS database showed that BMI is not a risk factors for poor patient and both liver and kidney graft survival (20). This study analyzed 7,205 SLK transplants.…”
Section: Pre-lt Obesitymentioning
confidence: 82%
“…The 1, 3 and 5 year overall patient survival, kidney and liver graft survivals were comparable between the three groups. Multivariate analysis identified diagnosis of hepatitis C, donor age, diabetes mellitus, and delayed kidney transplant function but not BMI as risk factors for poor patient and both liver and kidney graft survival (20). Additionally, a meta-analysis evaluating long-term impact of pre transplant obesity on patient survival in liver transplant recipients showed that BMI does not specifically impact patient survival.…”
Section: Pre-lt Obesitymentioning
confidence: 96%
“…The proportion of candidates with BMI ≥40 kg/m 2 continued to increase, and approximately one in six candidates (17%) are with BMI ≥35 kg/m 2 . 3 Several studies have reported con icting results on the impact of severe obesity on outcomes of LT. [4][5][6][7][8][9][10][11][12][13][14][15] Some centers and insurance payers have set a cutoff for BMI to list candidates at BMI >40 kg/m 2 . Currently, the American Association for the Study of Liver Disease considers morbid obesity (BMI ≥40 kg/m 2 ) as a relative contraindication for liver transplantation since these patients are at higher risk of post-transplant complications and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of candidates with BMI ≥ 40 kg/m2 continued to increase, and approximately one in six candidates (17%) are with BMI > 35 kg/m2. 4 Several studies have reported con icting results on the impact of severe obesity on outcomes of LT. [5][6][7][8][9][10][11][12][13][14][15][16] Some centers and insurance payers have set a cutoff for BMI to list candidates. Currently, the American Association for the Study of Liver Disease, in accordance with the American Society of Transplantation, considers morbid obesity (BMI ≥ 40 kg/m2) as a relative contraindication for liver transplantation, since these patients are at higher risk of post-transplant complications and mortality.…”
Section: Introductionmentioning
confidence: 99%